Agama, Budaya dan Perubahan Sosial Perspektif Pendidikan Islam di Aceh - Sri Astuti (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2017)
Religion and culture in Aceh are two entities that can not be interconnected with one another. Religion becomes a color for culture, on the contrary, cultural practices are equally strong. Once religion becomes a crystallized way of life in the systems, institutions and social structures that are built into a worldview. Similarly, in education that became the basis of dayah (pesantren) which serves as; transmission of Islamic sciences; Towards Islamic tradition; and ulama scholars. Then meunasah that serves other than as a place of religious education for religious education for children (Quran) as well as places of worship, meeting places and community gampong, religious studies for parents, centers of religious social activities, places of conflict resolution and dispute. The prolonged conflict between GAM and the Indonesian government and the tsunami has brought about a social change of Acehnese society, because of the strong foundation of Islamic education, the cohesion and social integration are well established.